ITRAQ-based proteomic analysis reveals several key metabolic pathways associated with male sterility in Salvia miltiorrhiza. Issue 29 (30th April 2020) - Wang, Ruihong; Lu, Congyu; Shu, Zhiming; Yuan, Xinbo; Jiang, Han; Guo, Hongbo
Abstract : Male sterility is a common phenomenon in flowering plants, and it has been widely used in hybrid seed production in a number of economically important crops. Abstract : Male sterility is a common phenomenon in flowering plants, and it has been widely used in hybrid seed production in a number of economically important crops. In 2002, our team discovered a natural male sterile mutant of Salvia miltiorrhiza . It provided us with the possibility of obtaining stable and controllable quality. To study the molecular mechanism of male sterility in S. miltiorrhiza, we generated proteomic profiles comparing the male sterile mutant type (MT) and wild type (WT) using iTRAQ sequencing. We found a total of 639 differential abundant proteins (DAPs) between MT and WT buds. The DAPs associated with male sterility were mainly involved in (1) carbohydrate and energy metabolism, and (2) protein synthesis and degradation. Based on a comparison between the protein expression profiles of MT and WT, we elucidated a potential protein interaction network involved in male sterility. These results provide new potential biomarkers and insights into the molecular mechanism of male sterility in S. miltiorrhiza .